Multi-omics Analysis Sheds Light on the Evolution and the Intracellular Lifestyle Strategies of Spotted Fever Group Rickettsia spp. - El Karkouri, Khalid; Kowalczewska, Malgorzata; Armstrong, Nicholas; Azza, Said; Fournier, Pierre-Edouard; Raoult, Didier (Frontiers in Microbiology, 2017)
Arthropod-borne Rickettsia species are obligate intracellular bacteria which are pathogenic for humans. Within this genus, R. slovaca and R. conorii cause frequent and potentially severe infections, whereas R. raoultii and R. massiliae cause rare and milder infections. All four species belong to spotted fever group (SFG) rickettsiae. However, R. slovaca and R. raoultii cause scalp eschar and neck lymphadenopathy (SENLAT) and are mainly associated with Dermacentor ticks, whereas the other two species cause Mediterranean spotted fever (MSF) and are mainly transmitted by Rhipicephalus ticks. To identify the potential genes and protein profiles and to understand the evolutionary processes that could, comprehensively, relate to the differences in virulence and pathogenicity observed between these four species, we compared their genomes and proteomes. The virulent and milder agents displayed divergent phylogenomic evolution in two major clades, whereas either SENLAT or MSF disease suggests a discrete convergent evolution of one virulent and one milder agent, despite their distant genetic relatedness. Moreover, the two virulent species underwent strong reductive genomic evolution and protein structural variations, as well as a probable loss of plasmid(s), compared to the two milder species. However, an abundance of mobilome genes was observed only in the less pathogenic species. After infecting Xenopus laevis cells, the virulent agents displayed less up-regulated than down-regulated proteins, as well as less number of identified core proteins. Furthermore, their similar and distinct protein profiles did not contain some genes (e.g., ompA/B and rickA) known to be related to rickettsial adhesion, motility and/or virulence, but may include other putative virulence-, antivirulence- and/or disease-related proteins. The identified evolutionary forces herein may have a strong impact on intracellular expressions and strategies in these rickettsiae, and that may contribute to the emergence of distinct virulence and diseases in humans. Thus, the current multi-omics data provide new insights into the evolution and fitness of SFG virulence and pathogenicity, and intracellular pathogenic bacteria.